GROWTH, YIELD,AND SEED QUALITY OF PEANUT GENOTYPESUNDER DROUGHT AND POOR NITROGENCONDITIONS - Hai, Nguyen; Hoang, Dinh; Chinh, Vu; Long, Nguyễn (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
This experiment was conducted in the spring cropping season of 2015 to evaluate growth, yield, and seed quality of peanut genotypes under drought and poor nitrogen field conditions at the Faculty of Agronomy, Vietnam National University of Agriculture. Seven high yielding peanut lines/cultivars and the Dau Giay cultivar (control) were laid out in a randomize complete block design with three replications. Irrigation was stopped for 45 days during the period from 30 to 75 days after sowing, then re-watered until harvest. Fertilizer (without nitrogen) was applied following the normal procedure. The results showed that under drought and poor nitrogen conditions, peanut genotypes performed well with a high tolerance to major diseases and insects, and had higher yields than the control (except for KKU60). D18 and Tainan9 showed the highest yields and thebest grain qualityunder drought and poor nutrient conditions. These two genotypes have the potential for development in drought and poor soil conditionsin Vietnam.